Polymer member-inorganic substrate composite, manufacturing method thereof, and polymer member therefor

By forming thermally modified polymer layers on inorganic substrates, polymeric members can be directly bonded without adhesives, enhancing adhesion and leveraging the unique properties of both materials.

JP7657246B2Active Publication Date: 2025-04-04TEIJIN LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023012003
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-04
Filing Date
2023-01-30
Publication Date
2025-04-04
Estimated Expiration
2040-03-06

AI Technical Summary

Technical Problem

Existing methods for bonding polymeric members to inorganic substrates often require the use of adhesives, which can limit the utilization of the unique properties of both materials.

Method used

A method involving the formation of thermally modified polymer layers on inorganic substrates, allowing for the direct bonding of polymeric members, including those with inorganic particles and coupling agents, without the need for adhesives.

Benefits of technology

This approach enhances the adhesion between polymeric members and inorganic substrates, improving the mechanical and thermal properties of the composite materials while eliminating the need for adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657246000014
    Figure 0007657246000014
  • Figure 0007657246000001
    Figure 0007657246000001
  • Figure 0007657246000002
    Figure 0007657246000002
Patent Text Reader

Abstract

A useful method for bonding a polymer member to an inorganic substrate without using an adhesive, and a polymer member used therefor, etc. are provided. [Solution] The present invention provides a polymer member-inorganic substrate composite, a method for producing the same, and a polymer member therefor. The method of the present invention for producing a polymer member-inorganic substrate composite (210, 220) includes providing a thermally modified polymer layer-inorganic substrate composite (110, 120) in which one or more thermally modified polymer layers (20, 21, 22) are in intimate contact with an inorganic substrate (10), and bonding a polymer member (30, 31, 32) to the inorganic substrate via the one or more thermally modified polymer layers (20, 21, 22).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer member-inorganic substrate composite, a method for producing the same, and a polymer member therefor. [Background technology]

[0002] Polymer members, for example, polyolefin-based polymer members such as polypropylene, polyethylene, and cycloolefin polymer, are excellent in lightness, mechanical strength, chemical resistance, etc., and are therefore widely used in molded products such as resin films, nonwoven fabrics, automobile parts, electrical equipment parts, camera lenses, etc. In contrast, inorganic materials such as metals, semiconductors, or oxides thereof have mechanical, thermal, optical, and chemical properties that differ from those of polymer members.

[0003] Therefore, it has been considered to bond polymeric members to inorganic substrates to advantageously take advantage of their different properties.

[0004] In this regard, for example, Patent Document 1 provides a composite material useful for microchips, liquid crystal protective films for televisions, etc., by integrating an inorganic material with a polyolefin resin material without using an adhesive. Specifically, Patent Document 1 proposes a method for producing a composite material having an inorganic material and a polyolefin resin material, in which a thin film having a thickness of 1 to 50 nm and made of an organic material having a hydrophilic group is formed on the surface of the inorganic material, the inorganic material and the polyolefin resin material on which the thin film has been formed are each irradiated with ultraviolet light having a wavelength of 100 to 200 nm, and then the polyolefin resin material is laminated on the thin film of the inorganic material to integrate the inorganic material and the polyolefin resin material. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-103456 A Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, it may be preferable to bond a polymer member to an inorganic substrate without using an adhesive. Therefore, the present invention provides a method useful for bonding a polymer member to an inorganic substrate without using an adhesive, and a polymer member and the like used therefor. [Means for solving the problem]

[0007] The present invention can be embodied in the following manner.

[0008] <Aspect 1> Providing a thermally modified polymer layer-inorganic substrate composite in which one or more thermally modified polymer layers are in close contact with an inorganic substrate; and bonding a polymeric member to the inorganic substrate via the one or more thermally modified polymer layers; Including, The polymer member includes at least inorganic particles and a polymer. A method for producing a polymer member-inorganic substrate composite. <Aspect 2> The method of embodiment 1, wherein the polymeric member further comprises a coupling agent. <Aspect 3> The method according to any one of the preceding claims, wherein the polymeric article is in the form of a membrane or film. <Aspect 4> The method according to any one of aspects 1 to 3, wherein the polymer members are bonded by thermocompression bonding. <Aspect 5> The method according to any one of aspects 1 to 4, wherein the one or more thermally alterable polymer layers are formed of an olefin polymer, and the polymer of the polymer member is an olefin polymer. <Aspect 6> The method of embodiment 5, wherein the olefin polymer is a cycloolefin polymer. Aspect 7 7. The method of any one of aspects 1-6, wherein the inorganic substrate is selected from the group consisting of metals and metalloids, oxides of metals and metalloids, nitrides of metals and metalloids, carbides of metals and metalloids, carbon materials, and combinations thereof. <Aspect 8> The present invention relates to a method for producing a substrate comprising: an inorganic substrate; one or more thermally modified polymer layers in close contact with the inorganic substrate; and a polymer member in close contact with the inorganic substrate via the one or more thermally modified polymer layers; The polymer member includes at least inorganic particles and a polymer. Polymer component-inorganic substrate composite. <Aspect 9> The composite of embodiment 8, wherein the polymeric member further comprises a coupling agent. Aspect 10 10. The composite according to claim 8 or 9, wherein the polymer member is in the form of a membrane or film. <Aspect 11> The composite according to any one of aspects 8 to 10, wherein the one or more thermally modified polymer layers are formed of an olefin polymer, and the polymer of the polymer member is an olefin polymer. Aspect 12 12. The composite of claim 11, wherein the olefin polymer is a cycloolefin polymer. Aspect 13 A polymeric component comprising at least inorganic particles, a polymer, and a coupling agent. Aspect 14 14. The polymeric article according to embodiment 13, which is in the form of a membrane or film. Aspect 15 15. The polymer member according to aspect 13 or 14, wherein the inorganic particles have an average primary particle size of 1 to 500 nm. Aspect 16 A polymer member including at least inorganic particles and a polymer; and An additional polymeric member, the additional polymeric member including at least a polymer. A composite polymer component comprising: Aspect 17 17. The composite polymer component according to claim 16, which is in the form of a membrane or film. Aspect 18 18. The composite polymer member according to aspect 16 or 17, wherein the inorganic particles have an average primary particle size of 1 to 500 nm. Aspect 19 19. The composite polymer member of any one of aspects 16 to 18, wherein at least one of the polymer member and the additional polymer member further comprises a coupling agent. <Aspect 20> The polymer member is in the form of a film and further comprises a coupling agent; The additional polymer member is in the form of a film, further comprises inorganic particles, and does not comprise a coupling agent; and It is in the form of a film. 20. The composite polymer member of embodiment 19. Aspect 21 The polymer member according to any one of embodiments 13 to 15, and the composite polymer member according to any one of embodiments 16 to 20, which are for optical use. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide a useful method for bonding a polymer member to an inorganic substrate without using an adhesive, and a polymer member and the like used therefor. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of a polymer member-inorganic substrate composite of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] <<Method for producing a polymer member-inorganic substrate composite>> The method of the present invention for producing a polymer member-inorganic substrate composite includes: Providing a thermally modified polymer layer-inorganic substrate composite in which one or more thermally modified polymer layers are in close contact with an inorganic substrate; and bonding the polymeric member to the inorganic substrate via the one or more thermally modified polymer layers; Includes.

[0012] Without being limited by theory, it is believed that the method of the present invention for producing a polymer component-inorganic substrate composite can improve the adhesion of the polymer component to the inorganic substrate by bonding the polymer component to the inorganic substrate via one or more thermally modified polymer layers. Here, with regard to bonding between the polymer component and the inorganic substrate via one or more thermally modified polymer layers, the polymer component can be bonded directly to one or more thermally modified polymer layers, or to a non-thermally modified polymer layer on the one or more thermally modified polymer layers.

[0013] A method for producing a thermally modified polymer layer-inorganic substrate composite having one or more thermally modified polymer layers intimately attached to an inorganic substrate can include forming a first polymer layer on the inorganic substrate and heating the first polymer layer to form a first thermally modified polymer layer, thereby intimately attaching the first thermally modified polymer layer to the inorganic substrate.

[0014] In the polymer member-inorganic substrate composite of the present invention, the polymer member contains at least inorganic particles and a polymer, and in particular contains at least inorganic particles and a cycloolefin polymer.

[0015] By containing inorganic particles in the polymer member in this manner, it becomes possible to adjust the physical properties of the polymer member, such as the refractive index.

[0016] In one preferred embodiment of the polymer component-inorganic substrate composite according to the present disclosure, the polymer component contains at least inorganic particles, a polymer, and a coupling agent, and in particular contains at least inorganic particles, a cycloolefin polymer, and a silane coupling agent.

[0017] By further containing a coupling agent in the polymer member, the adhesion of the polymer member to the thermally modified polymer layer can be further improved, particularly in cases where the adhesion of the polymer member to the thermally modified polymer layer is reduced due to the inclusion of inorganic particles.

[0018] Without being limited by theory, it is believed that this is because the coupling agent, particularly the coupling agent attached to the surface of the inorganic particles, improves the dispersibility of the inorganic particles in the polymeric material, while the remaining coupling agent improves the adhesion of the polymeric material to the thermally modified polymer layer.

[0019] <Inorganic base material> The inorganic substrate used in the method of the present invention may be any inorganic substrate, and may be selected from the group consisting of metals and metalloids, oxides of metals and metalloids, nitrides of metals and metalloids, carbides of metals and metalloids, carbon materials, and combinations thereof. Specifically, metals include aluminum, magnesium, titanium, nickel, chromium, iron, copper, gold, silver, tungsten, zirconium, yttrium, indium, iridium, etc., and metalloids include silicon, germanium, GaAs, InGaAs, InAlAs, LiTaO x , NbTaO x , ZnTe, GaSe, GaP, CdTe, diamond, diamond-like carbon, etc. can be mentioned. Therefore, examples of metal oxides include oxides of these metals, etc., and examples of semi-metal oxides include oxides of these semi-metals, etc. Examples of silicon oxides include glass such as quartz glass and soda glass, and examples of aluminum oxides include sapphire, etc. Examples of nitrides include aluminum nitride and silicon nitride, etc. Examples of carbides include silicon carbide. Examples of carbon materials include diamond, etc.

[0020] Inorganic substrates, particularly metals or metalloids, may be treated on their surfaces with ozone, ultraviolet light, or the like to increase the functional groups, e.g., hydroxyl groups, available for bonding with the first thermally modified polymer layer.

[0021] From the viewpoint of stably forming a thermally modified olefin polymer layer on an inorganic substrate, an inorganic material having a melting point higher than the thermal modification temperature of the thermally modified polymer layer can be preferably used.

[0022] The inorganic substrate may be in any shape, such as a film, sheet, plate, tube, rod, disk, etc. The inorganic substrate may be in any size.

[0023] <Thermal Modified Polymer Layer> A first polymer layer can be formed on the inorganic substrate, and the first polymer layer can be heated to become a first thermally modified polymer layer, thereby adhering the first thermally modified polymer layer onto the inorganic substrate.

[0024] Also, after forming the first thermally modified polymer layer, a second polymer layer can be formed on the first thermally modified polymer layer, and the second polymer layer can be heated to become a second thermally modified polymer layer, thereby adhering the second thermally modified polymer layer onto the first thermally modified polymer layer.

[0025] When a second thermally modified polymer layer is used, the degree of thermal modification of the second thermally modified polymer layer may be less than the degree of thermal modification of the first thermally modified polymer layer, so that the first thermally modified polymer layer provides good bonding with the inorganic substrate and the second thermally modified polymer layer provides good bonding with the first thermally modified polymer layer and the polymeric component.

[0026] Also, in the method of the present invention, after forming the second thermally modified polymer layer, a third polymer layer is formed on the second thermally modified polymer layer, and the third polymer layer is heated to become a third thermally modified polymer layer, thereby allowing the third thermally modified polymer layer to be adhered closely onto the second thermally modified polymer layer.

[0027] When a third heat-modified polymer layer is used, the degree of heat-modification of the third heat-modified polymer layer may be less than the degree of heat-modification of the second heat-modified polymer layer, so that the second heat-modified polymer layer provides good bonding with the first heat-modified polymer layer, and the third heat-modified polymer layer provides good bonding with the second heat-modified polymer layer and the polymeric component.

[0028] Additionally, fourth, fifth, etc. additional thermally alterable polymer layers may be used in a similar manner.

[0029] The degree of thermal modification of these thermally modified polymer layers can be adjusted by the heating temperature, time, surrounding atmosphere, etc. for the thermal modification.

[0030] Specifically, for example, the degree of thermal modification of the first thermally modified polymer layer may be the degree to which the first thermally modified polymer layer adheres to the inorganic substrate, i.e., the degree to which the adhesion of the first thermally modified polymer layer to the inorganic substrate is greater than the adhesion of the first polymer layer to the inorganic substrate before thermal modification.

[0031] Similarly, the degree of thermal modification of the second thermally modified polymer layer may be the degree to which the second thermally modified polymer layer adheres to the first thermally modified polymer layer, i.e., the degree to which the adhesion of the second thermally modified polymer layer to the first thermally modified polymer layer is greater than the adhesion of the second polymer layer to the first thermally modified polymer layer before thermal modification.

[0032] Similarly, the degree of thermal modification of the third thermally modified polymer layer may be the degree to which the third thermally modified polymer layer adheres to the second thermally modified polymer layer, i.e., the degree to which the adhesion of the third polymer layer to the second thermally modified polymer layer is greater than the adhesion of the third polymer layer to the second thermally modified polymer layer before thermal modification.

[0033] The degree of thermal modification of these thermally modified polymer layers can be adjusted, for example, by the heating temperature for thermal modification of the thermally modified polymer layer, the oxygen concentration in the atmosphere in which the heating is performed, etc. That is, in order to increase the degree of thermal modification, the heating temperature can be increased and / or the oxygen concentration in the atmosphere in which the heating is performed can be increased, and conversely, in order to decrease the degree of thermal modification, the heating temperature can be decreased and / or the oxygen concentration in the atmosphere in which the heating is performed can be decreased.

[0034] The heating temperature for the thermal modification of the thermally modified polymer layer may be 50° C. or more, 100° C. or more, 140° C. or more, 160° C. or more, 180° C. or more, or 200° C. or more, and may be 500° C. or less, 400° C. or less, 360° C. or less, 320° C. or less, or 280° C. or less. In addition, this heating can be performed in an oxygen-containing atmosphere, particularly in air.

[0035] The degree of thermal modification of these thermally modified polymer layers can be evaluated, for example, using the oxygen content of the thermally modified polymer constituting the thermally modified polymer layer, specifically, the ratio of the number of oxygen atoms contained in the thermally modified polymer layer to the total number of oxygen atoms and carbon atoms contained in the thermally modified polymer layer (number of oxygen atoms / (number of oxygen atoms+number of carbon atoms)×100(%)). In this case, it can be considered that the greater this ratio, the greater the degree of thermal modification. Here, X-ray photoelectron spectroscopy (XPS) can be used as a method for evaluating the oxygen and carbon atom contents of the thermally modified polymer layer, and K-Alpha (Thermo Fisher Scientific) can be used as an XPS device for this purpose.

[0036] When such a ratio (number of oxygen atoms / (number of oxygen atoms+number of carbon atoms)×100(%)) is 0.3% or more, 0.5% or more, 1.0% or more, 2.0% or more, or 5.0% or more, and 50% or less, 30% or less, 20% or less, 10% or less, or 8% or less, it is particularly appropriate to use it as an indicator of the degree of thermal modification of the thermally modified polymer layer.

[0037] When the degree of thermal modification is evaluated using the above ratio (number of oxygen atoms / (number of oxygen atoms+number of carbon atoms)×100(%)), the difference in this ratio between adjacent thermally modified polymer layers, such as the difference between this ratio in the first thermally modified polymer layer and this ratio in the second thermally modified polymer layer, may be 0.1% or more, 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.8% or more, 1.0% or more, 2.0% or more, or 3.0% or more, and may be 10.0% or less, 7.0% or less, 5.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, 0.5% or less, 0.3% or less, or 0.1 or less.

[0038] That is, for example, the ratio of the number of oxygen atoms contained in the second thermally modified polymer layer to the total number of oxygen atoms and carbon atoms contained in the second thermally modified polymer layer (i.e., the ratio of number of oxygen atoms / (number of oxygen atoms + number of carbon atoms) × 100 (%) for the second thermally modified polymer layer) may be 0.1% or more and 10.0% or less smaller than the ratio of the number of oxygen atoms contained in the first thermally modified polymer layer to the total number of oxygen atoms and carbon atoms contained in the first thermally modified polymer layer (i.e., the ratio of number of oxygen atoms / (number of oxygen atoms + number of carbon atoms) × 100 (%) for the first thermally modified polymer layer).

[0039] The degree of thermal denaturation of these thermally denatured polymer layers can be evaluated, for example, by the IR absorption spectrum of the thermally denatured polymer constituting the thermally denatured polymer layer, and Nicolet 6700 (Thermo Fisher Scientific) can be used as an IR absorption analyzer for this purpose. Specifically, the degree of thermal denaturation of the thermally denatured polymer layer can be evaluated by the ratio of the intensity of the absorption peak of C=O stretching vibration to the intensity of the absorption peak of C-H stretching vibration (ratio of the intensity of the absorption peak of C=O stretching vibration / intensity of the absorption peak of C-H stretching vibration (-)). In this case, the greater this ratio, the greater the degree of thermal denaturation can be considered. The intensity of the absorption peak can be obtained by reading the maximum value of the absorbance value of the absorption peak.

[0040] When such a ratio (the ratio of the absorption peak intensity of C=O stretching vibration / the absorption peak intensity (-) of C-H stretching vibration) is 0.01 or more, 0.02 or more, 0.05 or more, 0.1 or more, 0.15 or more, or 0.20 or more, and 20 or less, 10 or less, or 5 or less, it is particularly suitable to use it as an index representing the degree of thermal denaturation of the thermally denatured polymer layer.

[0041] When the degree of thermal denaturation is evaluated using the above ratio (ratio of the intensity of the absorption peak of C=O stretching vibration / intensity of the absorption peak of C-H stretching vibration (-)), the difference in this ratio between adjacent thermally denatured polymer layers, such as the difference between this ratio in the first thermally denatured polymer layer and this ratio in the second thermally denatured polymer layer, may be 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.8 or more, 1.0 or more, 2.0 or more, or 3.0 or more, and may be 10.0 or less, 7.0 or less, 5.0 or less, 3.0 or less, 2.0 or less, 1.0 or less, 0.5 or less, 0.3 or less, or 0.1 or less.

[0042] That is, for example, the ratio of the intensity of the absorption peak of the C=O stretching vibration of the second thermally modified polymer layer to the intensity of the absorption peak of the C-H stretching vibration of the second thermally modified polymer layer (i.e., the ratio of the intensity of the absorption peak of the C=O stretching vibration for the second thermally modified polymer layer / the intensity of the absorption peak of the C-H stretching vibration(-)) may be 0.1 or more and 20.0 or less smaller than the ratio of the intensity of the absorption peak of the C=O stretching vibration of the first thermally modified polymer layer to the intensity of the absorption peak of the C-H stretching vibration of the first thermally modified polymer layer (i.e., the ratio of the intensity of the absorption peak of the C=O stretching vibration for the first thermally modified polymer layer / the intensity of the absorption peak of the C-H stretching vibration(-)).

[0043] The heating method is not particularly limited, but may be a method using a heat source such as an oven, a hot plate, infrared rays, a flame, a laser, or a flash lamp.

[0044] The polymer layers, such as the first polymer layer, can be formed by coating and / or thermocompression bonding.

[0045] When the polymer layer is formed by coating, the polymer constituting the polymer layer is dissolved in a solvent to form a solution, and the solution is coated and dried to form the polymer layer. Examples of the coating method include a method using a solution such as spin coating, roll coater method, spray coating, die coater method, applicator method, dip coating method, brush coating, spatula coating, roller coating, curtain flow coater method, etc.

[0046] When a polymer layer such as the first polymer layer is formed by a method using a solution, a step of removing the solvent by heating after coating of the coating liquid can be included. In this case, the heating conditions can be selected to be a temperature, heating time, and atmospheric pressure conditions sufficient to remove the solvent from the coating film.

[0047] Furthermore, when the coating layer is formed by thermocompression, it can be performed by a method of melting or welding a bulk solid, powder, film, etc. while optionally applying pressure to press, such as a heat pressing method, welding method, powder coating method, etc.

[0048] The thickness of the polymer layer, such as the first polymer layer, may be any thickness that allows the resulting thermally modified polymer layer to provide good bonding between the inorganic substrate and the polymer member, and may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 100 μm or less, 30 μm or less, or 10 μm or less, or even 1000 nm or less, 500 nm or less, or 100 nm or less.

[0049] As described above, the thermally modified polymer layer is for bonding the polymer member to the inorganic substrate through the thermally modified polymer layer. Therefore, it is preferable that the thermally modified polymer layer is composed of the same type of polymer as the polymer constituting the polymer member in order to promote bonding between the thermally modified polymer layer and the polymer member.

[0050] Thus, for example, a polymer layer, such as the first polymer layer, may be formed of an olefin polymer, such as a cycloolefin polymer.

[0051] The olefin polymer means a polymer obtained by polymerizing a monomer containing an olefin as a main component, that is, a polymer obtained by polymerizing a monomer containing 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more of a monomer portion derived from an olefin. Examples of the olefin polymer include copolymers of α-olefin and ethylene or propylene, such as polyethylene, polypropylene, polybutene, polymethylpentene, propylene-ethylene copolymers and propylene-butene copolymers, styrene-butadiene-styrene block copolymers, styrene-hexadiene-styrene copolymers, styrene-pentadiene-styrene copolymers, ethylene-propylene-diene copolymers (RPDM), and cycloolefin polymers, but the present invention is not limited to these examples. These olefin polymers may be used alone or in combination of two or more types.

[0052] Among these olefin polymers, cycloolefin polymers can be mentioned in particular.

[0053] A cycloolefin polymer is a polymer having a cycloolefin moiety in the polymer main chain. Examples of such cycloolefin polymers include ring-opening polymers of cycloolefin monomers, addition polymers of cycloolefin monomers, and copolymers of cycloolefin monomers and chain olefins, but the present invention is not limited to these examples.

[0054] Cycloolefin monomers are compounds having a ring structure formed by carbon atoms and having a carbon-carbon double bond in the ring structure. Examples of cycloolefin monomers include norbornene-based monomers, which are monomers containing a norbornene ring, such as bicyclic monomers such as 2-norbornene and norbornadiene, tricyclic monomers such as dicyclopentadiene and dihydrodicyclopentadiene, tetracyclic monomers such as tetracyclododecene, ethylidenetetracyclododecene, and phenyltetracyclododecene, pentacyclic monomers such as tricyclopentadiene, and heptacyclic monomers such as tetracyclopentadiene; and monocyclic cycloolefins such as cyclobutene, cyclopentene, cyclooctene, cyclododecene, and 1,5-cyclooctadiene, but the present invention is not limited to these examples. Cycloolefin monomers may have a substituent within the scope of the present invention.

[0055] Cycloolefin polymers can be readily obtained commercially, for example, as products manufactured by Zeon Corporation under the trade names Zeonex series and Zeonor series, products manufactured by Sumitomo Bakelite Co., Ltd. under the trade name SUMILITE series, products manufactured by JSR Corporation under the trade name ARTON series, products manufactured by Mitsui Chemicals, Inc. under the trade name APEL series, products manufactured by Ticona under the trade name Topas, and products manufactured by Hitachi Chemical Co., Ltd. under the trade name OPTRETZ series.

[0056] In addition, when the polymer member is bonded to a non-thermally modified polymer layer on one or more heat-modified polymer layers, the non-thermally modified polymer layer is preferably the same type of polymer as the heat-modified polymer layer such as the first heat-modified polymer layer and the polymer member, and for example, the heat-modified polymer layer such as the first heat-modified polymer layer, the non-thermally modified polymer layer, and the polymer member may all be formed of an olefin polymer, for example, a cycloolefin polymer. For the specific material and formation method of the polymer member, the above description of the heat-modified polymer layer such as the first heat-modified polymer layer can be referred to.

[0057] Polymer Components In the method of the present invention, the polymer member may be a member of any shape, for example, a membrane or film. In this case, the polymer member can be bonded by coating or thermocompression, particularly thermocompression. Here, the polymer member at least contains inorganic particles and a polymer, and particularly preferably contains inorganic particles and at least a cycloolefin polymer. When the polymer member is in the form of a membrane or film, its preferred thickness is 1 cm or less, 5 mm or less, 2 mm or less, 1 mm or less, 500 μm or less, 200 μm or less, 100 μm or less, or 50 μm or less, and 1 μm or more, 2 μm or more, 5 μm or more, 10 μm or more, or 15 μm or more.

[0058] The polymeric component preferably further comprises a coupling agent, in particular a silane coupling agent.

[0059] Such a polymeric member may be an optical member, particularly an anti-reflection film. The polymeric member may be made of multiple parts, particularly a composite film that is a laminate of multiple layers. When the polymer member is a composite film which is a laminate of multiple layers, the number of layers in the laminate is preferably 2 or more, and is preferably 500 layers or less, 100 layers or less, 80 layers or less, 60 layers or less, 40 layers or less, 30 layers or less, 20 layers or less, 10 layers or less, or 5 layers or less.

[0060] The heat-modified polymer layer such as the first heat-modified polymer layer and the polymer member are preferably the same type of polymer, and for example, the heat-modified polymer layer such as the first heat-modified polymer layer and the polymer member may both be formed of an olefin polymer, for example, a cycloolefin polymer. For the specific polymer and forming method of the polymer member, the above description of the heat-modified polymer layer such as the first heat-modified polymer layer can be referred to.

[0061] (Inorganic particles) The inorganic particles in the present invention may include any inorganic particles that can be dispersed in a polymeric material, and such inorganic particles may include, for example, metal or semi-metal particles, metal or semi-metal oxide or fluoride particles, and particles of compounds containing metals or semi-metals.

[0062] As such a metal or semimetal, at least one selected from the group consisting of Si, Ge, Al, Mg, Ti, Ni, Cr, Fe, Cu, Au, Ag, W, Zr, Y, In, and Ir can be preferably used, and Si and Ge can be particularly preferably used. Furthermore, as such an oxide or fluoride of a metal or semimetal, MgO, Al2O3, Bi2O3, CaF2, In2O3, In2O3·SnO2, HfO2, La2O3, MgF2, Sb2O5, Sb2O5·SnO2, SiO2, SnO2, TiO2, Y2O3, ZnO, and ZrO 2、 At least one selected from the group consisting of the above can be preferably used, and MgO, Al2O3, SiO2, and TiO2 can be particularly preferably used. Also, examples of compounds containing such metals or semimetals include GaAs, InGaAs, InAlAs, LiTaO x , NbTaO x , ZnTe, GaSe, GaP, CdTe, diamond, diamond-like carbon, SiC, etc.

[0063] When the inorganic particles are silicon particles, examples of the silicon particles include silicon particles obtained by laser pyrolysis, particularly laser pyrolysis using a CO2 laser.

[0064] The inorganic particles, particularly silicon particles, may have individual impurity element concentrations of 1,000 ppm or less, 500 ppm or less, 300 ppm or less, 100 ppm or less, 50 ppm or less, 10 ppm or less, or 1 ppm or less to provide good optical properties. When the inorganic particles are silicon particles, such impurities may include Group 13 and Group 15 elements.

[0065] The average primary particle diameter of the inorganic particles is preferably 1 nm or more, or 3 nm or more, and 10,000 nm or less, 5,000 nm or less, 2,000 nm or less, 1,000 nm or less, 500 nm or less, 200 nm or less, 100 nm or less, 50 nm or less, 30 nm or less, 20 nm or less, or 10 nm or less.

[0066] Here, in the present invention, the average primary particle diameter of the particles can be determined as the number average primary particle diameter by directly measuring the particle diameter based on images taken by observation with a scanning electron microscope (SEM), a transmission electron microscope (TEM) or the like, and analyzing particle groups consisting of 100 or more aggregates.

[0067] If the particle size is too large, scattering may occur, which may be undesirable, while if the particle size is too small, the specific surface area of ​​the particles increases, promoting activation of the particle surface, and the cohesion between the particles increases significantly, which may be undesirable because handling properties are reduced.

[0068] The content ratio of the inorganic particles can be, for example, such that the volume ratio of the polymer to the inorganic particles is 1:99 to 99:1, 5:95 to 95:5, 10:90 to 85:15, 20:80 to 80:20, 30:70 to 75:25, or 40:60 to 70:30. If the amount of inorganic particles is too small, the degree of adjustment of the refractive index of the polymer member may be small, and if the amount of inorganic particles is too large, the strength of the polymer member may not be maintained. As described above, when the polymer member is composed of multiple parts, it is preferable that the part of the polymer member that is bonded to the thermally modified polymer layer-inorganic substrate composite satisfies the volume ratio of the polymer to the inorganic particles. Therefore, for example, when the polymer member is a composite film that is a laminate of multiple layers, it is preferable that the layer of the composite film that is bonded to the thermally modified polymer layer-inorganic substrate composite satisfies the volume ratio of the polymer to the inorganic particles.

[0069] As the coupling agent in the present invention, any coupling agent that can be combined with inorganic particles can be used. Specifically, as the coupling agent, a silane coupling agent, a titanate coupling agent, or an aluminate coupling agent can be used, and in particular, a silane coupling agent can be used. When an olefin polymer, for example, a cycloolefin polymer, is used as the polymer of the polymer member, as the coupling agent, a coupling agent having a functional group with good miscibility with these polymers, for example, an alkyl chain, a cyclohexyl group, or a benzene ring, more specifically, a coupling agent having an alkyl chain, a cyclohexyl group, or a benzene ring having 1 to 30, 1 to 25, or 1 to 20 carbon atoms can be used. The coupling agent and / or the hydrolysis condensate of the coupling agent may be used alone or in combination of two or more kinds.

[0070] Specifically, examples of the coupling agent include octadecyltriethoxysilane (OTS), octyltriethoxysilane, triethoxyphenylsilane, 3-phenylpropyltriethoxysilane, cyclohexyltrimethoxysilane, octadecyltrimethoxysilane, octadecyltrichlorosilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride, Examples of suitable silanes include N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltriethoxysilane hydrochloride, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, vinyltriacetoxysilane, γ-anilinopropyltrimethoxysilane, γ-anilinopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, octadecyldimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(triethoxysilyl)propyl]ammonium chloride, γ-ureidopropyltrimethoxysilane, γ-ureidopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, and 3-isocyanatopropyltriethoxysilane.

[0071] The content ratio of the coupling agent can be, for example, such that the mass ratio of the inorganic particles to the coupling agent is 1:99 to 99:1, 5:95 to 95:5, 10:90 to 90:10, 20:80 to 80:20, 30:70 to 70:30, or 40:60 to 60:40. If the amount of the coupling agent is too small, the adhesion between the polymer member and the thermally modified polymer layer may be insufficient, and if the amount of the coupling agent is too large, the strength, etc. of the polymer member may not be maintained.

[0072] Polymer-inorganic composite In the thermally modified polymer layer-inorganic substrate composite that can be used for the production of the polymer member-inorganic substrate composite of the present invention, one or more thermally modified polymer layers are adhered to the inorganic substrate. In the polymer member-inorganic substrate composite of the present invention, the polymer member is adhered to the inorganic substrate via one or more thermally modified polymer layers of the thermally modified polymer layer-inorganic substrate composite of the present invention.

[0073] Specifically, as shown in Figures 1(a) and (b), in the polymer member-inorganic substrate composite 210, 220 of the present invention, the polymer members 30, 31, 32 are bonded to the inorganic substrate 10 via one or more thermally modified polymer layers 20, 21, 22 of the thermally modified polymer layer-inorganic substrate composite 110, 120.

[0074] According to such a polymer member-inorganic substrate composite of the present invention, the adhesion of the polymer member to the inorganic substrate can be improved.

[0075] For details of each component of the thermally modified polymer layer-inorganic substrate composite of the present invention and the polymer member-inorganic substrate composite of the present invention, the description relating to the method of the present invention can be referred to. <Composite polymer components>

[0076] A polymeric component according to the present disclosure may be combined with an additional polymeric component comprising at least a polymer to form a composite polymeric component.

[0077] With regard to the additional polymer member, reference may be made to the description regarding the polymer member, except that the additional polymer member may not contain inorganic particles. EXAMPLES

[0078] Examples 1 to 9 and Comparative Example 1 In Examples 1 to 9, as shown in FIG. 1(b), a laminate having first and second thermally modified polymer layers 21, 22, and first and second antireflection layers 31, 32 as polymer members, in that order, was formed on a silicon substrate 10, and the adhesion of the composite antireflection film consisting of the first and second antireflection layers to the silicon substrate was evaluated for this laminate.

[0079] In addition, in Comparative Example 1, a laminate having first and second antireflection layers in this order as polymer members was formed on a silicon substrate, and the adhesion of the composite antireflection film consisting of the first and second antireflection layers to the silicon substrate was evaluated for this laminate.

[0080] In Examples 1 to 9 and Comparative Example 1, cycloolefin polymer (COP) (Zeonex (trademark) 480R, glass transition temperature 138° C., manufactured by Zeon Corporation) was used as the material for both the thermally modified polymer layer and the polymer member.

[0081] Example 1 (1) Preparation of COP solution A COP solution A was obtained by mixing and stirring 7% by mass of COP and 93% by mass of toluene at room temperature.

[0082] (2) Preparation of a composite antireflection film having a first and a second antireflection film (a) Preparation of COP solution B1 (without silicon particles) COP solution B1 was obtained by mixing and stirring 35% by weight of COP and 65% by weight of toluene at room temperature.

[0083] (b) Preparation of COP solution B2 (containing OTS-treated silicon particles) (b-1) Preparation of silicon particles Silicon particles were produced by laser pyrolysis (LP) using a carbon dioxide laser with monosilane gas as the raw material. The metal impurity contents of the obtained silicon particles were measured using an inductively coupled plasma mass spectrometer (ICP-MS), and the Fe content was 15 ppb, Cu content was 18 ppb, Ni content was 10 ppb, Cr content was 21 ppb, Co content was 13 ppb, Na content was 20 ppb, and Ca content was 10 ppb. The average primary particle size of the inorganic particles was 100 nm.

[0084] (b-2) Surface treatment of silicon particles Silicon particles and octadecyltriethoxysilane (OTS) were mixed in a sealed container in amounts such that the weight ratio of silicon particles to OTS was 1:1 (mass ratio), and then the mixture was heated to 120°C and held for 3 hours to obtain OTS-treated silicon particles.

[0085] (b-3) Preparation of COP solution B2 A COP solution was obtained by mixing and stirring 10% by mass of COP and 90% by mass of toluene at room temperature. The OTS-treated silicon particles were added to and mixed with this COP solution so that the volume ratio of COP to silicon particles was 65:35. The mixture was then dispersed with a homogenizer for 15 minutes to prepare a COP solution B2 containing OTS-treated silicon particles.

[0086] (c) Preparation of composite anti-reflection film (c-1) Formation of the second antireflection layer The COP solution B1 obtained as described above was applied onto a glass plate using a doctor blade to obtain a coating film, and the coating film was heated at 110°C to remove the solvent in the coating film, thereby obtaining a second antireflection layer having a thickness of 25 μm on the glass plate.

[0087] (c-2) Formation of the first antireflection layer The COP solution B2 obtained as described above was applied onto the second antireflection layer using a doctor blade to obtain a coating film, and the coating film was heated at 110°C to remove the solvent in the coating film, thereby forming a first antireflection layer with a thickness of 20 μm on the second antireflection layer with a thickness of 25 μm.

[0088] (c-3) Peeling off the composite anti-reflective film The first and second antireflection layers obtained as described above were peeled off from the glass plate to obtain a composite antireflection film (composite polymer member) having the first and second antireflection layers.

[0089] (3) Formation of the first thermally modified polymer layer The COP solution A was spin-coated onto a silicon substrate as an inorganic base material by maintaining a rotation speed of 2000 rpm for 20 seconds.

[0090] The silicon substrate thus coated with COP solution A was then held on a hot plate heated to 120° C. and dried to obtain a silicon substrate with a first polymer layer. The substrate was then held on a hot plate heated to 280° C. for 1 minute to thermally denature the first polymer layer, thereby bonding the first thermally denatured polymer layer with a thickness of 23 nm to the silicon substrate.

[0091] (4) Formation of a second thermally modified polymer layer The first thermally denatured polymer layer of the silicon substrate obtained as described above was spin-coated with COP solution A. The spin-coating was performed by maintaining a rotation speed of 2000 rpm for 20 seconds.

[0092] The silicon substrate thus coated with COP solution A was then held on a hot plate heated to 120° C. and dried to form a second polymer layer on the first thermally modified polymer layer. The substrate was then held on a hot plate heated to 200° C. for 2 minutes to thermally modify the second polymer layer, thereby forming a second thermally modified polymer layer with a thickness of 23 nm in close contact with the first thermally modified polymer layer.

[0093] (5) Bonding of composite anti-reflection film The composite antireflection film obtained as above was adhered to the second thermally modified polymer layer of the silicon substrate obtained as above, so that the first antireflection layer was in contact with the second thermally modified polymer layer, and the composite antireflection film was adhered to the second thermally modified polymer layer by thermocompression bonding at a temperature of 115°C and a pressure of 0.2 MPa for 60 minutes. The obtained evaluation laminate had the first thermally modified polymer layer, the second thermally modified polymer layer, the first antireflection layer, and the second antireflection layer in this order on the silicon substrate.

[0094] (Cross-cut test) The laminate for evaluation obtained as described above was subjected to a cross-cut test.

[0095] Specifically, a cutter knife was used to make cuts at 1 mm intervals in the composite anti-reflection film formed on a silicon substrate, reaching the silicon substrate. After making six cuts, six more cuts were made perpendicular to the first cuts, forming a checkerboard pattern.

[0096] Then, Scotch mending tape (3M, 810, width 24 mm) was applied to the surface of the polymeric member, and the tape was rubbed with a finger to make it adhere, and then the tape was peeled off. The areas where the tape was applied and peeled off in this way were observed under a stereomicroscope.

[0097] The evaluation results were classified as follows: A: The edges of the cut were completely smooth, and no peeling was observed on any of the grid cells. B: The polymeric material experienced partial delamination, but less than 35% of the crosscut area was affected. C: The polymer component underwent major peeling over the entire surface, with 35% or more of the cross-cut area affected. D: The adhesion of the polymer part to the substrate was poor, so the cross-cut test was not performed.

[0098] In the composite anti-reflective film of Example 1, the edges of the cuts were completely smooth, and no peeling was observed in any of the lattice meshes (evaluation A). The preparation conditions and evaluation results of the evaluation laminate of Example 1 having the first and second thermally modified polymer layers and the first and second anti-reflective layers on the silicon substrate are shown in Table 1 below.

[0099] Examples 2 to 8 Except for the fact that the method for forming the second antireflection layer was a spray method (Example 2), and that the volume ratio of COP to silicon particles in the COP solution for preparing COP solution B2 was changed (Examples 3 to 8), the evaluation laminates of Examples 2 to 8 having first and second thermally modified polymer layers and first and second antireflection layers on a silicon substrate were obtained in the same manner as in Example 1. The evaluation laminates of Examples 2 to 8 were evaluated in the same manner as in Example 1. The preparation conditions and evaluation results for the evaluation laminates of Examples 2 to 8 are shown in Table 1 below.

[0100] Example 9 A laminate for evaluation having first and second thermally modified polymer layers and first and second antireflection layers on a silicon substrate was obtained in the same manner as in Example 1, except that in the manufacturing process of COP solution B2, surface treatment of silicon particles using OTS was not performed and COP solution B2' (containing non-OTS-treated silicon particles) was obtained, and this COP solution B2' was used instead of COP solution B2. The laminate for evaluation of Example 9 was evaluated in the same manner as in Example 1. The preparation conditions and evaluation results for the laminate for evaluation of Example 9 are shown in Table 1 below.

[0101] Comparative Example 1 Except for not forming the first and second thermally modified polymer layers, an evaluation laminate having a first and second antireflection layer on a silicon substrate was obtained in the same manner as in Example 9. This evaluation laminate of Comparative Example 1 was evaluated in the same manner as in Example 1. The preparation conditions and evaluation results for the evaluation laminate of Comparative Example 1 are shown in Table 1 below.

[0102] Example 10 A laminate for evaluation having first and second thermally modified polymer layers and first to fourth antireflection layers on a silicon substrate was obtained in the same manner as in Example 1, except for the following points: (i) The COP solution B1 was applied onto a glass plate using a doctor blade to obtain a coating film, and the coating film was heated at 110° C. to remove the solvent in the coating film, thereby obtaining a fourth antireflection layer having a thickness of 25 μm on the glass plate; (ii) after the above (i), the COP solution B2 was applied onto the fourth antireflection layer using a doctor blade to obtain a coating film, and the coating film was heated at 110°C to remove the solvent in the coating film, thereby obtaining a third antireflection layer having a thickness of 20 μm on the fourth antireflection layer; (iii) after the above (ii), the COP solution B1 was applied onto the third antireflection layer using a doctor blade to obtain a coating film, and the coating film was heated at 110°C to remove the solvent in the coating film, thereby obtaining a second antireflection layer having a thickness of 25 μm on the third antireflection layer; (iv) After the above (iii), COP solution B2 was applied onto the second antireflection layer using a doctor blade to obtain a coating film, and the coating film was heated at 110°C to remove the solvent in the coating film, thereby obtaining a first antireflection layer having a thickness of 20 μm on the second antireflection layer.

[0103] This laminate for evaluation of Example 10 was evaluated in the same manner as in Example 1. The preparation conditions and evaluation results for the laminate for evaluation of Example 10 are shown in Table 2 below.

[0104] Example 11 A laminate for evaluation having first and second thermally modified polymer layers and first to third antireflection layers on a silicon substrate was obtained in the same manner as in Example 1, except for the following points: (i) The COP solution B1 was applied onto a glass plate using a doctor blade to obtain a coating film, and the coating film was heated at 110° C. to remove the solvent in the coating film, thereby obtaining a third antireflection layer having a thickness of 25 μm on the glass plate; (ii) After the above (i), the COP solution B2' used in Example 9, i.e., the COP solution containing silicon particles not surface-treated with OTS, was applied onto the third antireflection layer using a doctor blade to obtain a coating film, and the coating film was heated at 110°C to remove the solvent in the coating film, thereby obtaining a second antireflection layer having a thickness of 15 μm on the third antireflection layer. (iii) After the above (ii), COP solution B2 was applied onto the second antireflection layer using a doctor blade to obtain a coating film, and the coating film was heated at 110°C to remove the solvent in the coating film, thereby obtaining a first antireflection layer having a thickness of 5 μm on the second antireflection layer.

[0105] This laminate for evaluation of Example 11 was evaluated in the same manner as in Example 1. The preparation conditions and evaluation results for the laminate for evaluation of Example 11 are shown in Table 2 below.

[0106] [Table 1]

[0107] [Table 2]

[0108] A comparison between Examples 1 to 11 and Comparative Example 1 shows that the adhesion of the antireflective film to the inorganic substrate is improved by bonding the antireflective film (polymer member) to the inorganic substrate via a thermally modified polymer layer.

[0109] Furthermore, as can be seen from Tables 1 and 2, when the antireflective film (polymer member) contains a coupling agent, it is understood that the adhesion between the thermally modified polymer layer and the antireflective film is further improved even when the antireflective layer contains inorganic particles.

[0110] Reference Examples 1 to 14 and Comparative Examples 1 to 2 In the following Reference Examples and Reference Comparative Examples, the formation of a thermally modified polymer layer and the adhesion of a polymer member to the thermally modified polymer layer are evaluated.

[0111] The polymers used to form the thermally modified polymer layers and polymer members in the following reference examples are as follows: COP1: Cycloolefin polymer (Arton (trademark) (JSR Corporation)) COP2: Cycloolefin polymer (Zeon Corporation, Zeonex(trademark) 480R, glass transition temperature 138°C)

[0112] Reference Examples 1 to 14 and Comparative Examples 1 to 2 As described below, COP1 was used as the material for both the thermally modified polymer layer and the polymer member in Reference Examples 1 to 14. In Reference Comparative Examples 1 and 2, COP1 was used as the material for the polymer member without using a thermally modified polymer layer.

[0113] <Reference example 1> (Preparation of solution for thermally modified polymer layer) A solution for a thermally modified polymer layer was obtained by mixing and stirring 7% by mass of COP1 and 93% by mass of chloroform at room temperature.

[0114] (Formation of the first thermally modified polymer layer) The solution for the thermally denaturable polymer layer was spin-coated onto a silicon substrate as an inorganic base material by maintaining a rotation speed of 2000 rpm for 20 seconds.

[0115] The silicon substrate thus coated with the solution for the thermally modified polymer layer was then placed on a hot plate heated to 120°C to dry the solution for the thermally modified polymer layer, thereby obtaining a silicon substrate with a first polymer layer. The substrate was then placed on a hot plate heated to 280°C for 1 minute to thermally modify the first polymer layer, thereby obtaining a silicon substrate with a first thermally modified polymer layer having a thickness of 23 nm.

[0116] (Formation of the second thermally modified polymer layer) The solution for forming the thermally modified polymer layer was spin-coated onto the first thermally modified polymer layer of the silicon substrate obtained as described above. The spin-coating was performed by maintaining a rotation speed of 2000 rpm for 20 seconds.

[0117] Thereafter, the silicon substrate coated with the thermally modified polymer layer solution was held on a hot plate heated to 120°C, and the thermally modified polymer layer solution was dried to form a second polymer layer on the first thermally modified polymer layer. The substrate was then held on a hot plate heated to 200°C for 2 minutes to thermally modify the second polymer layer, and a second thermally modified polymer layer having a thickness of 23 nm was adhered to the first thermally modified polymer layer. The thermally modified polymer layer-inorganic substrate composite thus obtained was used as the thermally modified polymer layer-inorganic substrate composite of Reference Example 1.

[0118] (Preparation of solutions for polymer components) 7% by mass of COP1 and 93% by mass of chloroform were mixed and stirred at room temperature to obtain a solution for the polymer member.

[0119] (Joining of polymer components) The second thermally modified polymer layer thus obtained was spin-coated with a solution for the polymer member by maintaining a rotation speed of 2000 rpm for 20 seconds.

[0120] Thereafter, the silicon substrate coated with the polymer member solution in this manner was held on a hot plate heated to 140° C. for 10 minutes to dry the polymer member solution, and a polymer member having a film thickness of 23 nm was bonded onto the second thermally modified polymer layer. The polymer member-inorganic substrate composite thus obtained was used as the polymer member-inorganic substrate composite of Reference Example 1.

[0121] (Cross-cut test) Using a cutter knife, cuts were made at 1 mm intervals in the first and second thermally modified polymer layers and the laminate of the polymer members formed on the silicon substrate, reaching the silicon substrate. After making the six cuts, six more cuts were made perpendicular to the cuts to form a grid pattern.

[0122] Then, Scotch mending tape (3M, 810, width 24 mm) was applied to the surface of the polymeric member, and the tape was rubbed with a finger to make it adhere, and then the tape was peeled off. The areas where the tape was applied and peeled off in this way were observed under a stereomicroscope.

[0123] The evaluation results were classified as follows: A: The edges of the cut were completely smooth, and no peeling was observed on any of the grid cells. B: The polymeric material experienced partial delamination, but less than 35% of the crosscut area was affected. C: The polymer component underwent major peeling over the entire surface, with 35% or more of the cross-cut area affected.

[0124] In the polymer member-inorganic substrate composite of Reference Example 1, the edges of the cuts were completely smooth, and no peeling was observed in any of the lattice meshes (evaluation A). The preparation conditions and evaluation results of this composite material are shown in Table R1 below.

[0125] <Reference examples 2~8> Except for changing the concentration of the polymer in the solution for forming the thermally modified polymer layer (Reference Examples 2 and 3), the spin coating conditions in the solution for forming the thermally modified polymer layer (Reference Example 4), and the temperature of thermal modification of the first thermally modified polymer (Reference Examples 5 to 8) as shown in Tables R1 and 2, polymer member-inorganic substrate composites of Reference Examples 2 to 8 were prepared in the same manner as Reference Example 1 and evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of these composite materials are shown in Tables R1 and 2 below.

[0126] <Reference example 3A> (Formation of First and Second Thermally Modified Polymer Layers) A first thermally modified polymer layer and a second thermally modified polymer were formed on a silicon substrate in the same manner as in Reference Example 1, except that the thermal modification temperature of the first thermally modified polymer was 300°C, and the thermal modification temperature of the second thermally modified polymer was 280°C and the treatment time was 1 minute.

[0127] (Formation of the third thermally modified polymer layer) The solution for forming the thermally-modifiable polymer layer was spin-coated onto the second thermally-modifiable polymer layer obtained as described above. The spin-coating was carried out by maintaining a rotation speed of 2000 rpm for 20 seconds.

[0128] Thereafter, the silicon substrate coated with the thermally modified polymer layer solution was held on a hot plate heated to 120°C, and the thermally modified polymer layer solution was dried to form a third polymer layer on the second thermally modified polymer layer. The substrate was then held on a hot plate heated to 200°C for 2 minutes to thermally modify the third polymer layer, and a third thermally modified polymer layer having a thickness of 23 nm was adhered to the second thermally modified polymer layer. The thermally modified polymer layer-inorganic substrate composite thus obtained was used as the thermally modified polymer layer-inorganic substrate composite of Reference Example 3A.

[0129] (Joining of polymer components) Thereafter, the polymer members were joined in the same manner as in Reference Example 1 to prepare a polymer member-inorganic substrate composite of Reference Example 3A.

[0130] (Cross-cut test) The polymer member-inorganic substrate composite of Reference Example 3A was evaluated in the same manner as in Reference Example 1.

[0131] The preparation conditions and evaluation results of this composite material are shown in Table R1 below.

[0132] Comparative Example 1 Except for the fact that COP1 was spin-coated directly onto a silicon substrate as an inorganic substrate without forming the first and second thermally modified polymer layers on the silicon substrate, a polymer member-inorganic substrate composite of Reference Comparative Example 1 was prepared in the same manner as in Reference Example 1, and was evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Tables R1 and R2 below.

[0133] <Reference example 9> In bonding the polymer members, instead of spin-coating a cycloolefin polymer, a film of COP1 (thickness 100 μm) was placed on the second thermally modified polymer layer and held at a pressure of 50 MPa and a temperature of 140° C. for 2 hours to thermocompress this film and the second thermally modified polymer layer, except that a polymer member-inorganic substrate composite of Reference Example 9 was prepared in the same manner as Reference Example 1 and evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R3 below.

[0134] Comparative Example 2 A polymer member-inorganic substrate composite of Reference Comparative Example 2 was prepared in the same manner as in Reference Example 9, except that a film of COP1 (thickness: 100 μm) was thermocompression-bonded directly onto a silicon substrate as an inorganic substrate without forming first and second thermally modified polymer layers on the silicon substrate, and was evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R3 below.

[0135] <Reference examples 10~14> After forming a first thermally modified polymer layer on a silicon substrate as an inorganic substrate, polymer member-inorganic substrate composites of Reference Examples 10 to 14 were prepared in the same manner as Reference Examples 5, 6, 1, 7, and 8, respectively, except that a second thermally modified polymer layer was not formed and the polymer member solution was spin-coated directly onto the first thermally modified polymer layer, and the composites were evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of these composite materials are shown in Table R4 below.

[0136] Reference Examples 15 to 20 and Comparative Example 3 As described below, COP2 was used as the material for both the thermally modified polymer layer and the film of the polymer member in Reference Examples 15 to 20. In Reference Comparative Example 3, no thermally modified polymer layer was used, and COP2 was used as the material for the film of the polymer member.

[0137] <Reference example 15> In the preparation of both the thermally modified polymer layer solution and the polymer member solution, 10% by mass of COP2 and 90% by mass of toluene were mixed and stirred at room temperature to obtain the thermally modified polymer layer solution, and the polymer member-inorganic substrate composite of Reference Example 15 was prepared in the same manner as in Reference Example 1, except that it was evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R5 below.

[0138] <Reference example 16> Except for changing the concentration of the polymer in the solution for forming the thermally modified polymer layer from 10% by mass to 1% by mass, a polymer member-inorganic substrate composite of Reference Example 16 was prepared in the same manner as in Reference Example 15, and evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R5 below.

[0139] Comparative Example 3 A polymer member-inorganic substrate composite of Reference Comparative Example 3 was prepared in the same manner as in Reference Example 15, except that COP2 was spin-coated directly onto a silicon substrate as an inorganic substrate without forming the first and second thermally modified polymer layers on the silicon substrate, and was evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R5 below.

[0140] <Reference examples 17~20> Except for changing the thermal modification temperature of the first thermally modified polymer as shown in Table R6, polymer member-inorganic substrate composites of Reference Examples 17 to 20 were prepared in the same manner as Reference Example 15, and evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of these composite materials are shown in the following Table R6.

[0141] Reference Example 21 and Reference Comparative Example 4 As described below, a polyethylene (PE) film (thickness 30 μm) was used as the material for both the thermally modified polymer layer and the polymer member in Reference Example 21. In Reference Comparative Example 4, a polyethylene film (thickness 30 μm) was used as the material for the polymer member without using a thermally modified polymer layer.

[0142] <Reference example 21> (Formation of the first thermally modified polymer layer) A polyethylene film (thickness: 30 μm) was placed on a silicon substrate as an inorganic substrate, and the substrate was heated to 120° C. and held for 1 minute to obtain a silicon substrate with a polyethylene film. This substrate was then held for 1 minute on a hot plate heated to 280° C. to thermally modify the polyethylene film, thereby obtaining a silicon substrate with a first thermally modified polymer layer.

[0143] (Formation of the second thermally modified polymer layer) A polyethylene film (thickness 30 μm) was placed on the first thermally modified polymer layer of the silicon substrate obtained as described above, and the substrate was heated to 120 ° C. and held for 1 minute to attach the polyethylene film to the first thermally modified polymer layer. The substrate was then held on a hot plate heated to 200 ° C. for 2 minutes to thermally modify the polyethylene film, thereby adhering the second thermally modified polymer layer to the first thermally modified polymer layer. The thermally modified polymer layer-inorganic substrate composite thus obtained was designated as the thermally modified polymer layer-inorganic substrate composite of Reference Example 21.

[0144] (Joining of polymer components) A polyethylene film (thickness 30 μm) was placed on the second thermally modified polymer layer obtained as described above, and the substrate was heated to 120 ° C. and held for 1 minute, and then the substrate was further heated to 140 ° C. and held for 10 minutes, thereby bonding the polyethylene film as a polymer member onto the first thermally modified polymer layer. The polymer member-inorganic substrate composite thus obtained was used as the polymer member-inorganic substrate composite of Reference Example 21, and was evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R7 below.

[0145] Comparative Example 4 A polymer member-inorganic substrate composite of Reference Comparative Example 4 was prepared in the same manner as in Reference Example 21, except that a polyethylene film as a polymer member was directly bonded onto a silicon substrate as an inorganic substrate without forming the first and second thermally modified polymer layers on the silicon substrate, and was evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R7 below.

[0146] 《Reference examples 22~27》 As described below, in Reference Examples 22 to 27, different polymers were used for the material of the thermally modified polymer layer and the material of the polymer member.

[0147] <Reference Examples 22 and 23> (Formation of First and Second Thermally Modified Polymer Layers) As in Reference Example 1, first and second thermally modified polymer layers were formed on a silicon substrate as an inorganic substrate using COP1.

[0148] (Joining of polymer components) In Reference Example 22, the polymer member solution of COP2 obtained as in Reference Example 15 was spin-coated on the second thermally modified polymer layer obtained as described above, and dried to prepare a polymer member-inorganic substrate composite of Reference Example 22, which was evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R8 below.

[0149] In Reference Example 23, a polyethylene film (thickness 30 μm) was bonded onto the second thermally modified polymer layer obtained as described above in the same manner as in Reference Example 21 to prepare a polymer member-inorganic substrate composite of Reference Example 23, which was evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R8 below.

[0150] <Reference Examples 24 and 25> (Formation of First and Second Thermally Modified Polymer Layers) As in Reference Example 15, first and second thermally modified polymer layers were formed on a silicon substrate as an inorganic substrate using COP2.

[0151] (Joining of polymer components) In Reference Example 24, the polymer member solution of COP1 obtained as in Reference Example 1 was spin-coated on the second thermally modified polymer layer obtained as described above, and dried to prepare a polymer member-inorganic substrate composite of Reference Example 24, which was evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R8 below.

[0152] In Reference Example 25, a polyethylene film (thickness: 30 μm) was bonded onto the second thermally modified polymer layer obtained as described above in the same manner as in Reference Example 21 to prepare a polymer member-inorganic substrate composite of Reference Example 25, which was evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R8 below.

[0153] <Reference Examples 26 and 27> (Formation of First and Second Thermally Modified Polymer Layers) As in Reference Example 21, first and second thermally modified polymer layers were formed on a silicon substrate as an inorganic substrate using a polyethylene film (thickness: 30 μm).

[0154] (Joining of polymer components) In Reference Example 26, the polymer member solution of COP1 obtained as in Reference Example 1 was spin-coated onto the second thermally modified polymer layer obtained as described above, and dried to prepare a polymer member-inorganic substrate composite of Reference Example 26, which was evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R8 below.

[0155] In Reference Example 27, the polymer member solution of COP2 obtained as in Reference Example 15 was spin-coated on the second thermally modified polymer layer obtained as above, and dried to prepare a polymer member-inorganic substrate composite of Reference Example 26, which was evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R8 below.

[0156] Reference Examples 28 to 30 and Comparative Examples 5 to 7 <Reference examples 28~30> Except for using a silicon substrate (Reference Example 28), a copper plate (Reference Example 29), and an aluminum plate (Reference Example 30) each having a SiN layer formed on the surface thereof instead of a silicon substrate as the inorganic substrate, polymer member-inorganic substrate composites of Reference Examples 28 to 30 were prepared in the same manner as Reference Example 15, and evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of these composite materials are shown in Table R9 below.

[0157] Comparative Examples 5 to 7 Polymer member-inorganic substrate composites of Reference Comparative Examples 5 to 7 were prepared in the same manner as in Reference Examples 28 to 30, except that no thermally modified polymer layer was used, and were evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of these composite materials are shown in the table below.

[0158] Comparative Examples 8 to 13 As described below, in Comparative Reference Examples 8 to 13, a silicon substrate as an inorganic substrate was treated with a silane coupling agent, and a polymer member was bonded to the treated surface.

[0159] Comparative Examples 8-9 A silicon substrate as an inorganic substrate was subjected to ultraviolet light and ozone treatment (UV / O3 treatment), and then held in a saturated vapor pressure atmosphere of octadecyltriethoxysilane (OTS) as a silane coupling agent at 150°C for 3 hours to obtain an OTS-treated silicon substrate.

[0160] In Reference Comparative Example 8, a polymer member was bonded to the surface of the OTS-treated silicon substrate thus obtained by spin coating without forming a thermally modified polymer layer, in the same manner as in Reference Example 15, to prepare a polymer member-inorganic substrate composite of Reference Comparative Example 8, which was then evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R10 below.

[0161] In Reference Comparative Example 9, a polymer member-inorganic substrate composite of Reference Comparative Example 9 was prepared by bonding a polymer member by thermocompression bonding in the same manner as in Reference Example 21 without forming a thermally modified polymer layer on the surface of the OTS-treated silicon substrate thus obtained, and was evaluated in the same manner as in Reference Example 1. The preparation conditions and evaluation results of this composite material are shown in Table R10 below.

[0162] Comparative Examples 10 to 11 Except for using 3-phenylpropyltriethoxysilane (PTS) instead of octadecyltriethoxysilane (OTS) as the silane coupling agent, polymer member-inorganic substrate composites of Reference Comparative Examples 10 to 11 were prepared in the same manner as Reference Comparative Examples 8 and 9, respectively, and evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of these composite materials are shown in Table R10 below.

[0163] Comparative Examples 12 to 13 Except for using 3-aminopropyltriethoxysilane (ATS) instead of octadecyltriethoxysilane (OTS) as the silane coupling agent, polymer member-inorganic substrate composites of Reference Comparative Examples 12 to 13 were prepared in the same manner as Reference Comparative Examples 8 and 9, respectively, and evaluated in the same manner as Reference Example 1. The preparation conditions and evaluation results of these composite materials are shown in Table R10 below.

[0164] [Table 3]

[0165] [Table 4]

[0166] [Table 5]

[0167] [Table 6]

[0168] [Table 7]

[0169] [Table 8]

[0170] [Table 9]

[0171] [Table 10]

[0172] [Table 11]

[0173] [Table 12]

[0174] Evaluation Results From Table R1 above, it can be seen that when the polymer concentration in the polymer solution for forming the thermally modified polymer layer is set to 1% by mass to 7% by mass and the spin coating rotation speed when forming the thermally modified polymer layer is set to 2000 rpm to 4000 rpm (Reference Examples 1 to 4), peeling of the polymer component is suppressed compared to when no thermally modified polymer layer is used (Reference Comparative Example 1).

[0175] Furthermore, from Table R1 above, it can be seen that peeling of the polymer component is suppressed not only when the thermally modified polymer layer is two layers (Reference Examples 1 to 4), but also when the thermally modified polymer layer is three layers (Reference Example 3A), compared to when no thermally modified polymer layer is used (Reference Comparative Example 1).

[0176] From Table R2 above, it can be seen that when the thermal modification temperature for forming the thermally modified polymer layer is set to a temperature of 200°C to 360°C (Reference Examples 1 and 5 to 8), peeling of the polymer component is suppressed compared to when no thermally modified polymer layer is used (Reference Comparative Example 1).

[0177] From Table R3 above, it can be seen that when a polymer member film is thermocompression bonded to a thermally modified polymer layer (Reference Example 9), peeling of the polymer member is suppressed compared to when a polymer member is thermocompression bonded directly to a silicon substrate without using a thermally modified polymer layer (Reference Comparative Example 2).

[0178] From Table R4 above, it can be seen that even when only one thermally modified polymer layer is used rather than two layers (Reference Examples 10 to 14), peeling of the polymer component is suppressed compared to when no thermally modified polymer layer is used (Reference Comparative Example 1).

[0179] From Table R5 above, it can be seen that when the polymer concentration in the polymer solution for forming the thermally modified polymer layer is 1% by mass to 10% by mass (Reference Examples 15 to 16), peeling of the polymer component is suppressed compared to when no thermally modified polymer layer is used (Reference Comparative Example 3).

[0180] From Table R6 above, it can be seen that when the thermal modification temperature for forming the thermally modified polymer layer is set to a temperature of 200°C to 360°C (Reference Examples 10 and 17 to 20), peeling of the polymer component is suppressed compared to when no thermally modified polymer layer is used (Reference Comparative Example 3).

[0181] From Table R7 above, it can be seen that when a polymer component film is bonded to a thermally modified polymer layer by thermocompression (Reference Example 21), peeling of the polymer component is suppressed compared to when a polymer component film is bonded directly to a silicon substrate by thermocompression without using a thermally modified polymer layer (Reference Comparative Example 4).

[0182] From Table R8 above, it can be seen that even under conditions in which the polymer for forming the thermally modified polymer layer and the polymer for forming the polymer member are different, when a thermally modified polymer layer is used (Reference Examples 22 to 27), peeling of the polymer member is suppressed compared to when a thermally modified polymer layer is not used (Reference Comparative Examples 1, 3, and 4).

[0183] From Table R9 above, it can be seen that even under conditions in which the substrate is not a silicon substrate but a silicon substrate with SiN formed on the surface, a copper plate, or an aluminum plate, peeling of the polymer component is suppressed when a thermally modified polymer layer is used (Reference Examples 28 to 30) compared to when a thermally modified polymer layer is not used (Reference Comparative Examples 5 to 7).

[0184] From Table R10 above, it can be seen that even when the substrate is a silicon substrate treated with a silane coupling agent, peeling of the polymer component is not suppressed compared to the case where a thermally modified polymer layer is used (reference example).

[0185] 《Reference examples 31-36》 A silicon substrate with a thermally modified polymer layer was obtained on a silicon substrate as an inorganic substrate in the same manner as in Reference Example 1, except that a solution for the thermally modified polymer layer was obtained by mixing and stirring 20 mass% COP1 and 80 mass% chloroform at room temperature, and the temperature of the hot plate for thermal modification was set to 400°C (Reference Example 31), 320°C (Reference Example 32), 280°C (Reference Example 33), 240°C (Reference Example 34), 200°C (Reference Example 35), and 160°C (Reference Example 36).

[0186] (Elemental analysis by XPS) For the thermally modified polymer layers of Reference Examples 31 to 36, an XPS device (K-Alpha (Thermo Fisher Scientific)) was used to determine the ratio of the number of oxygen atoms contained in the thermally modified polymer layer to the total number of oxygen atoms and carbon atoms contained in the thermally modified polymer layer (number of O atoms / (number of O atoms+number of C atoms) (%)).

[0187] The X-ray source was monochromated AlKα radiation, and the photoelectron take-off angle was set to 0 degrees. The O1s peak area was determined by drawing a baseline in the range of 527-537 eV according to the Shirley method, and the C1s peak area was determined by drawing a baseline in the range of 280-290 eV according to the Shirley method. The oxygen concentration and oxygen concentration on the film surface were determined by correcting the above O1s peak area and C1s peak area with the sensitivity coefficient specific to each device.

[0188] The preparation conditions and evaluation results of this thermally modified polymer layer are shown in the following Table R11. From this Table R11, it can be seen that as the temperature for thermal modification decreases, that is, as the degree of thermal modification decreases, this ratio (number of O atoms / (number of O atoms+number of C atoms)(%)) decreases, and therefore this ratio can be used as an index of the degree of thermal modification of the thermally modified polymer layer.

[0189] (Infrared absorption spectrum measurement) The thermally modified polymer layers of Reference Examples 31 to 36 were analyzed by infrared absorption spectrometry (Nicolet 6700 (Thermo Fisher Scientific)) at 4000 to 500 cm -1 By measuring the infrared transmission absorption spectrum in the range of 2947 cm -1 The intensity of the CH stretching vibration absorption peak with a peak at 1732 cm -1 The ratio of the intensity of the absorption peak of the C=O stretching vibration to the peak at 100 nm (the ratio of the intensity of the absorption peak of the C=O stretching vibration / the intensity of the absorption peak of the C-H stretching vibration (-)) was calculated. The intensity of the absorption peak was calculated by reading the maximum value of the absorbance of the absorption peak.

[0190] The preparation conditions and evaluation results of this thermally modified polymer layer are shown in the following Table R11. From this Table R11, it can be seen that as the temperature for thermal modification decreases, that is, as the degree of thermal modification decreases, this ratio (the ratio of the intensity of the absorption peak of C=O stretching vibration / the intensity of the absorption peak of C-H stretching vibration (-)) decreases, and therefore this ratio can be used as an index of the degree of thermal modification of the thermally modified polymer layer.

[0191] [Table 13] [Explanation of symbols]

[0192] 10 Inorganic substrate 20, 21, 22 Thermally modified polymer layer 30, 31, 32 Polymer parts 110, 120 Thermally modified polymer layer-inorganic substrate composite 210, 220 Polymer member-inorganic substrate composite of the present invention

Claims

1. A polymeric member, The polymer member-inorganic substrate composite is used for producing a polymer member-inorganic substrate composite by bonding to an inorganic substrate via one or more thermally modified polymer layers, the one or more thermally modified polymer layers being thermally modified by heating a polymer layer formed from a polymer having 50% by mass or more of a monomer portion derived from a cycloolefin in an oxygen-containing atmosphere; The polymer member is The composition is formed from inorganic particles, a polymer having a monomer portion derived from cycloolefin of 50% by mass or more, and a coupling agent; The thickness is 1 μm or more and 1 cm or less, The volume ratio of the polymer to the inorganic particles is 5:95 to 95:5; A polymer component for optical applications.

2. The polymer article according to claim 1 , which is in the form of a membrane or a film.

3. The polymer member according to claim 1 or 2, wherein the inorganic particles have an average primary particle size of 1 to 500 nm.

4. A composite polymer member, comprising a polymer member and an additional polymer member, The composite polymer member is used to manufacture a composite polymer member-inorganic substrate composite by bonding to an inorganic substrate via one or more thermally modified polymer layers, the polymer member of the composite polymer member being in direct contact with the one thermally modified polymer layer or with one of the plurality of thermally modified polymer layers that is the furthest from the inorganic substrate, the one or more thermally modified polymer layers being thermally modified by heating a polymer layer formed from a polymer having 50% by mass or more of a monomer portion derived from a cycloolefin in an oxygen-containing atmosphere, the polymer member is formed from inorganic particles and a polymer having 50 mass % or more of a monomer portion derived from a cycloolefin, has a thickness of 1 μm or more and 1 cm or less, and has a volume ratio of the polymer to the inorganic particles of 5:95 to 95:5; the additional polymer component is formed from a polymer having 50% by weight or more of a monomer portion derived from a cycloolefin; Composite polymer components for optical applications.

5. The composite polymer component according to claim 4 , which is in the form of a membrane or film.

6. The composite polymer member according to claim 4 or 5, wherein the inorganic particles have an average primary particle size of 1 to 500 nm.

7. The composite polymer component according to any one of claims 4 to 6, wherein the polymer component and / or the further polymer component further comprises a coupling agent.

8. The polymer member is in the form of a film and further comprises a coupling agent; The additional polymer member is in the form of a film, further comprises inorganic particles, and does not comprise a coupling agent; and It is in the form of a film. The composite polymer component of claim 7.

9. The present invention relates to a method for producing a substrate comprising: an inorganic substrate; one or more thermally modified polymer layers in close contact with the inorganic substrate; and a polymer member in close contact with the inorganic substrate via the one or more thermally modified polymer layers; The polymer member is formed from inorganic particles and a polymer having 50% by mass or more of a monomer portion derived from a cycloolefin. A polymer member-inorganic substrate composite, the one or more thermally modified polymer layers include a first thermally modified polymer layer; the first thermally modified polymer layer is a thermally modified polymer layer obtained by heating a polymer layer formed from a polymer having 50% by mass or more of a monomer portion derived from a cycloolefin in an oxygen-containing atmosphere; the ratio of the number of oxygen atoms contained in the first thermally denaturable polymer layer (the number of oxygen atoms / (the number of oxygen atoms+the number of carbon atoms)×100(%)) is 0.3% or more and 30% or less; Polymer component-inorganic substrate composite.

10. The present invention relates to a method for manufacturing a substrate, comprising: an inorganic substrate; a plurality of thermally modified polymer layers in close contact with the inorganic substrate; and a polymer member in close contact with the inorganic substrate via the plurality of thermally modified polymer layers; The polymer member is formed from inorganic particles and a polymer having 50% by mass or more of a monomer portion derived from a cycloolefin. A polymer member-inorganic substrate composite, the plurality of thermally modified polymer layers include a first thermally modified polymer layer in close contact with the inorganic base material, and a second thermally modified polymer layer in close contact with the first thermally modified polymer layer; each of the first thermally modified polymer layer and the second thermally modified polymer layer is a thermally modified polymer layer obtained by heating a polymer layer formed from a polymer having 50% by mass or more of a monomer portion derived from a cycloolefin in an oxygen-containing atmosphere; a difference between the ratio of the number of oxygen atoms contained in the first thermally denatured polymer layer (the number of oxygen atoms / (the number of oxygen atoms+the number of carbon atoms)×100(%)) and the ratio of the number of oxygen atoms contained in the second thermally denatured polymer layer (the number of oxygen atoms / (the number of oxygen atoms+the number of carbon atoms)×100(%)) is 0.3% or more and 10% or less; Polymer component-inorganic substrate composite.

11. The composite of claim 9 or 10, wherein the polymeric material further comprises a coupling agent.

12. The composite according to any one of claims 9 to 11, wherein the polymer member is in the form of a membrane or a film.

Citation Information

Patent Citations

  • Composite material and method of manufacturing the same

    JP2013103456A

  • Optical functional film and manufacturing method therefor

    JP2016212193A

  • Optical film, optical film manufacturing method, and polarizer

    JP2017116759A

  • Insulation resin material

    JP2018141158A

  • Resin film forming film and resin film forming composite sheet

    WO2019008898A1